Full-spectrum correlated-k-distribution look-up table for radiative transfer in nonhomogeneous participating media with gas-particle mixtures. (July 2019) - Wang, Chaojun; He, Boshu; Modest, Michael F.
Highlights: Two schemes were proposed to combine radiative properties of gas and particle. The FSK-FSK scheme employed the correlation principle. The FSK-Gray scheme used the Planck-mean absorption coefficients of particles. Both accuracy and efficiency of the two schemes were verified. Abstract: The full-spectrum correlated- k -distribution (FSCK) look-up table previously developed by the authors Wang et al. (2018) provides an efficient means for accurate calculations of radiative properties of gas-soot mixtures. Except for those of soot, radiative properties of particles are impossible to tabulate in FSCK look-up tables since particles of different compositions and sizes may have different local temperatures. In order to combine the radiative properties of particles with those of gas-soot mixtures from the FSCK look-up table, two schemes named gas FSK-particle FSK (FSK-FSK) and gas FSK-particle Gray (FSK-Gray) schemes, are proposed. The FSK-FSK scheme employs the correlation principle to obtain the radiative properties of gas-particle mixtures in FSCK form on-the-fly while the FSK-Gray scheme uses the Planck-mean absorption coefficient to represent particle spectral behavior. Several radiative heat transfer calculations across a 1D slab are carried out to test the accuracy of the two schemes. Furthermore, radiative heat transfer in a realistic coal flame and a scaled version of it are determined to validate the performance of the developed scheme. Results show that use of either scheme gives results of excellent accuracy with extremely low computational cost compared to benchmark line-by-line results.